The intersection of mineralocorticoid receptor activation and the FGF23–Klotho cascade: a duopoly that promotes renal and cardiovascular injury. Issue 2 (30th August 2021) - Epstein, Murray; Freundlich, Michael
Abstract: The nexus of chronic kidney disease (CKD) and cardiovascular disease (CVD) amplifies the morbidity and mortality of CKD, emphasizing the need for defining and establishing therapeutic initiatives to modify and abrogate the progression of CKD and concomitant CV risks. In addition to the traditional CV risk factors, disturbances of mineral metabolism are specific risk factors that contribute to the excessive CV mortality in patients with CKD. These risk factors include dysregulations of circulating factors that modulate phosphate metabolism, including fibroblast growth factor 23 (FGF23) and soluble Klotho. Reduced circulating levels and suppressed renal Klotho expression may be associated with adverse outcomes in CKD patients. While elevated circulating concentrations or locally produced FGF23 in the strained heart exert prohypertrophic mechanisms on the myocardium, Klotho attenuates tissue fibrosis, progression of CKD, cardiomyopathy, endothelial dysfunction, vascular stiffness and vascular calcification. Mineralocorticoid receptor (MR) activation in nonclassical targets, mediated by aldosterone and other ligands, amplifies CVD in CKD. In concert, we detail how the interplay of elevated FGF23, activation of the MR and concomitant reductions of circulating Klotho in CKD may potentiate each other's deleterious effects on the kidney and heart, thereby contributing to the initiation and progression of kidney and cardiac functional deterioration, acting through multipronged, albeit complementary, mechanistic pathways.